Colours of the fraud - Štajn, Otilija (knjige, 2024)
What would you do if you found out the painting in your bedroom is worth a million? A cancelled meeting unravels Ema's life. As head of finance, her career begins to fall apart, and uncertainty suffocates her. Mojca, the woman she loves, is slipping away. At her thirty-fifth birthday party, things worsen when a guest identifies a nude woman depicted in an oil painting as his deceased sister—killed in a car accident in Ljubljana twenty years ago. "Colours of the Fraud" places Ema in the spotlight. Faced with business fraud, she must make a tough choice. Will she chase financial gain, risking losing Mojca and the genuine bond they share? Or will she reclaim her integrity and find true self-acceptance? As her quest deepens, so do the stakes—her career, her loving lesbian relationship, and her very identity hang in the balance. And what secrets does the enigmatic painting hold, weaving its threads into Ema’s fate? The answers await discovery within the pages of her tale.